The Role of Affect in Attentional Functioning for Younger and Older Adults - Noh, Soo Rim; Larcom, Mary Jo; Liu, Xiaodong; Isaacowitz, Derek (Frontiers in Psychology, 2012)
Although previous research has shown that positive affect (PA) and negative affect (NA) modulate attentional functioning in distinct ways, few studies have considered whether the links between affect and attentional functioning may vary as a function of age. Using the Attention Network Test (Fan, McCandliss, Sommer, Raz, & Posner, 2002), we tested whether participants’ current state of PA and NA influenced distinct attentional functions (i.e., alerting, orienting, and executive attention) and how the relationships between affective states and attentional functioning differ in younger (18-25 yrs) and older (60-85 yrs) age groups. The results revealed that higher PA was associated with lower alerting efficiency; however, this pattern did not vary by age group. While there were age differences in alerting efficiency, these age differences were mediated by PA, indicating that the higher state PA found in older adults may contribute to age differences in alerting. Furthermore, age group moderated the relationship between PA and orienting as well as NA and orienting. That is, higher levels of PA and lower levels of NA were associated with enhanced orienting efficiency in older adults. Neither PA nor NA had any influence on executive attention. The current results suggest that positive and negative affect may influence attentional functioning in distinct ways, but that these patterns may depend on age groups.